Impact of a surgical approach for implantation of durable left ventricular assist devices in patients on extracorporeal life support. Issue 4 (5th February 2021) - Potapov, Evgenij; Loforte, Antonio; Pappalardo, Federico; Morshuis, Michiel; Schibilsky, David; Zimpfer, Daniel; Lewin, Daniel; Riebandt, Julia; Von Aspern, Konstantin; Stein, Julia; Attisani, Matteo; Haneya, Assad; et al.
Abstract: Background: The aim of this study was to evaluate the impact of the surgical approach on the postoperative outcome in patients who underwent left ventricular assist device (LVAD) implantation after having received veno‐arterial extracorporeal life support (va‐ECLS) using data from a European registry (ECLS‐VAD). Five hundred and thirty‐one patients were included. Methods: A propensity score‐adjusted outcome analysis was performed, resulting in 324 patients in the full sternotomy (FS) group and 39 in the less invasive surgery (LIS) group. Results: The surgery lasted in median 236 min in the FS group versus 263 min in the LIS group ( p = 0.289). The median chest tube output during the first 24 h was similar in both groups. Patients who underwent implantation with an FS required more blood products during the first 24 postoperative hours (median 16 vs. 12, p = 0.033). The incidence of revision due to bleeding was also higher (35.5 vs. 15.4%, p = 0.016). A temporary postoperative right ventricular assist device was necessary in 45.1 (FS) versus 23.1% (LIS) of patients, respectively ( p = 0.067). No stroke occurred in the LIS group during the first 30 days after surgery (7.4% in the FS group). The incidence of stroke and of renal, hepatic, and respiratory failure during the follow‐up was similar in both groups. The 30‐day and one‐year survival were similar in both groups. Conclusion: LIS for implantation of a durable LVAD in patients on va‐ECLS implanted for cardiogenic shock is associated with less revision due to bleeding, less administration of blood products and absence of perioperative stroke, with no impact on survival.